2023
DOI: 10.2196/37318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Unmet Social Needs, Scarcity, and Future Discounting on Adherence to Treatment in Children With Asthma: Protocol for a Prospective Cohort Study

Abstract: Background Asthma is one of the most prevalent chronic diseases of childhood and disproportionately affects children with lower socioeconomic status. Controller medications such as inhaled corticosteroids significantly reduce asthma exacerbations and improve symptoms. However, a large proportion of children still have poor asthma control, in part owing to suboptimal adherence. Financial barriers contribute to hindering adherence, as do behavioral factors related to low income. For example, unmet so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 101 publications
2
0
0
Order By: Relevance
“…Some studies indicated that medication adherence was lower among those with financial difficulties and consideration of the medical expenses as high, which matched those observed in our study ( Liu et al, 2022 ; Drouin et al, 2023 ). Most medications for CPP are the original brands with expensive prices in China, and our study showed that 49.6% of families considered that the medication was expensive and 21.6% of them had difficulty in paying for the medical expenses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some studies indicated that medication adherence was lower among those with financial difficulties and consideration of the medical expenses as high, which matched those observed in our study ( Liu et al, 2022 ; Drouin et al, 2023 ). Most medications for CPP are the original brands with expensive prices in China, and our study showed that 49.6% of families considered that the medication was expensive and 21.6% of them had difficulty in paying for the medical expenses.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also found that caregivers in the poor medication adherence group had a worse cognition of the harm of noncompliance with medication, which is in agreement with Zhang et al's findings (Zhang et al, 2022). Caregivers with a lower cognition of medication adherence were more likely to present Some studies indicated that medication adherence was lower among those with financial difficulties and consideration of the medical expenses as high, which matched those observed in our study (Liu et al, 2022;Drouin et al, 2023). Most medications for CPP are the original brands with expensive prices in China, and our study showed that 49.6% of families considered that the medication was expensive and 21.6% of them had difficulty in paying for the medical expenses.…”
Section: Discussionsupporting
confidence: 85%